A Systematic Review of the Cost-Utility of Spinal Cord Stimulation for Persistent Low Back Pain in Patients With Failed Back Surgery Syndrome. Issue 1 (April 2021) - McClure, Jesse J.; Desai, Bhargav D.; Ampie, Leonel; You, Wen; Smith, Justin S.; Buchholz, Avery L.
Study Design: Systematic Review. Objectives: To review the literature surrounding the cost-effectiveness of implanting spinal cord stimulators for failed back surgery syndrome. Methods: A systematic review was conducted inclusive of all publications in the Medline database and Cochrane CENTRAL trials register within the last 10 years (English language only) assessing the cost-effectiveness of Spinal Cord Stimulator device implantation (SCSdi) in patients with previous lumbar fusion surgery. Results: The majority of reviewed publications that analyzed cost-effectiveness of SCSdi compared to conventional medical management (CMM) or re-operation in patients with failed back surgery syndrome (FBSS) showed an overall increase in direct medical costs; these increased costs were found in nearly all cases to be offset by significant improvements in patient quality of life. The cost required to achieve these increases in quality adjusted life years (QALY) falls well below 25 000/QALY, a conservative estimate of willingness to pay. Conclusions: The data suggest that SCSdi provides both superior outcomes and a lower incremental cost: effectiveness ratio (ICER) compared to CMM and/or re-operation in patients with FBSS. These findings are in spite of the fact that the majority of studies reviewed were agnostic to the type of device or innervation utilized in SCSdi. Newer devices utilizing burst or higher frequency stimulation have demonstrated their superiority over traditional SCSdi via randomized clinical trials and may provide lower ICERs.